2021
DOI: 10.1177/1362361320984317
|View full text |Cite
|
Sign up to set email alerts
|

Core experiences of parents of children with autism during the COVID-19 pandemic lockdown

Abstract: The lockdown that was imposed by governments as part of the attempt to contain the COVID-19 pandemic included extreme measures, such as home confinement and the shutting down of special education systems. Our aim was to learn about the core experiences of parents of children with autism during this significant life disturbance. Thirty-one parents of 25 children with autism participated in semi-structured telephone interviews which were transcribed verbatim and underwent a qualitative, immersion/crystallization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
131
1
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(156 citation statements)
references
References 44 publications
7
131
1
17
Order By: Relevance
“…This additional burden was greater for children with disabilities, such as intellectual disabilities and ASD, due to difficulties related to understanding, communicating, and coping with such changes [ 58 ]. School closures and social distancing resulted in many children with disabilities stopping crucial services and therapies, decreasing class attendance, and interrupting social relationships, academic, and work routines [ 59 , 60 ••, 61 65 , 66 •, 67 •, 68 ••]. Additionally, studies reported alterations of sleep patterns [ 61 , 66 •, 67 •, 69 – 74 ], eating habits [ 66 •, 67 •, 75 ], and decreased physical activity [ 67 •, 76 ] among children with disabilities during this time.…”
Section: Covid-19 Pandemicmentioning
confidence: 99%
See 4 more Smart Citations
“…This additional burden was greater for children with disabilities, such as intellectual disabilities and ASD, due to difficulties related to understanding, communicating, and coping with such changes [ 58 ]. School closures and social distancing resulted in many children with disabilities stopping crucial services and therapies, decreasing class attendance, and interrupting social relationships, academic, and work routines [ 59 , 60 ••, 61 65 , 66 •, 67 •, 68 ••]. Additionally, studies reported alterations of sleep patterns [ 61 , 66 •, 67 •, 69 – 74 ], eating habits [ 66 •, 67 •, 75 ], and decreased physical activity [ 67 •, 76 ] among children with disabilities during this time.…”
Section: Covid-19 Pandemicmentioning
confidence: 99%
“…School closures and social distancing resulted in many children with disabilities stopping crucial services and therapies, decreasing class attendance, and interrupting social relationships, academic, and work routines [ 59 , 60 ••, 61 65 , 66 •, 67 •, 68 ••]. Additionally, studies reported alterations of sleep patterns [ 61 , 66 •, 67 •, 69 – 74 ], eating habits [ 66 •, 67 •, 75 ], and decreased physical activity [ 67 •, 76 ] among children with disabilities during this time. Child welfare agencies also described decreases in reports of child abuse/neglect, likely due to fewer opportunities for identification posed by school closures, lockdowns, and social distancing [ 77 ].…”
Section: Covid-19 Pandemicmentioning
confidence: 99%
See 3 more Smart Citations